(untitled) (Agricultural Engineering, 2020)
The article presents the results of tensile strength tests taking into account the influence of the printing nozzle diameter. The 3D printing method in FDM technology is described. The aim of the research was to investigate the effect of the printing nozzle diameter installed in the head. Samples printed with two types of filling were tested. The obtained results were summarized and compared. The printing time of the samples was compared with a diameter of each nozzle. Based on the strength tests, it can be concluded that the tensile strength of the samples made with the FDM printing technology is proportional to the used printing nozzle diameter.